(untitled) (Archaeologia Adriatica, 2022)
Visibility traces that represent subsurface context, such as soil marks or crop marks, are common phenomena for detecting archaeological sites by using aerial archaeology as one of remote sensing methods, through the medium of oblique aerial photography. Various discussions and use of aerial archaeology method in general are mostly limited to regions with continental climate that contain an abundance of cultivated soil. Remote sensing methods reveal archaeological sites in karst landscape mostly as surface structures, and not as subsurface archaeological context that is represented or mediated by soil marks and crop marks. Results of the aerial survey of Velebit mountain, a part of the North Dalmatian plateau and the Obrovac plateau in Croatia are presented in this paper. Analysis of oblique aerial photographs was conducted with the aim of systematization of visibility indicators for the archaeological sites in the Dinaric karst landscape. Visibility indicators that enable discovering archaeological sites depend on karst relief, sub-Mediterranean climate and scrub vegetation. It has been determined that archaeological sites can be recognized by indicators such as shadow, texture, colour and vegetation by using the method of aerial archaeology. Defined indicators in cultural landscape in the karst area that were used for detection of archaeological sites are rarely represented independently. Archaeological sites are usually visible owing to combination of several individual indicators.